1993
DOI: 10.1159/000196176
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Echocardiographic Assessment of Right Cardiac Pressure Overload in Patients with Chronic Obstructive Airway Disease

Abstract: Two-dimensional echocardiography was used to estimate right cardiac pressure overload in patients with chronic obstructive airway disease. Area measurements of the four heart chambers were carried out from the apical four-chamber view. Additionally, the respiratory behaviour of the inferior vena cava was examined from the subcostal view. A good apical imaging of the four-chamber view for area measurement was obtained in 44 out of 48 patients with chronic obstructive airway disease. The respiratory behaviour of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Therefore, assessment of additional criteria like right heart chamber volumes and CS diameter may be useful for the prediction of RAP. Machraouni et al 13 found a good correlation between pulmonary artery mean pressure and the area index of the two right heart cavities (r = 0.83) and between RAP and RA area index (r = 0.64). In the study of Raymond et al, 16 RA area index was also closely correlated with RAP (r = 0.72, P < 0.001).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, assessment of additional criteria like right heart chamber volumes and CS diameter may be useful for the prediction of RAP. Machraouni et al 13 found a good correlation between pulmonary artery mean pressure and the area index of the two right heart cavities (r = 0.83) and between RAP and RA area index (r = 0.64). In the study of Raymond et al, 16 RA area index was also closely correlated with RAP (r = 0.72, P < 0.001).…”
Section: Discussionmentioning
confidence: 95%
“…Use of the size and inspiratory collapsibility of the VCI is the most widely adopted method for the estimation of RAP 9 . Although, a number of studies report a high correlation (0.57–0.93) between TTE and right heart catheterization measurements of PASP, 1 discrepancies have been observed between RAP estimated by the pattern of VCI collapse and measured by right heart catheterization 6,7,13,14 . Vena cava measurements depend on the image being obtained perpendicular to the vessel, and in addition, there may be differences in the collapsibility of the VCI based on variations in inspiratory effort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a dilated right atrium is a sign of increased RA pressure. Machraouni et al (15) reported a strong correlation between RA pressure and the RA area index (r=0.64). However, this is a qualitative measure that does not allow the interpreter to assess RA pressure (6).…”
Section: Discussionmentioning
confidence: 98%